The Efficacy of Intense Pulsed Light Combined With Meibomian Gland Expression for the Treatment of Dry Eye Disease Due to Meibomian Gland Dysfunction: A Multicenter, Randomized Controlled Trial - Yan, Xiaoming; Hong, Jing; Jin, Xiuming; Chen, Wei; Rong, Bei; Feng, Yun; Huang, Xiaodan; Li, Jinyang; Song, Wenjing; Lin, Lin; Cheng, Yu (Eye & contact lens, 2021)
To compare the efficacy of intense pulsed light (IPL) combined with Meibomian gland expression (MGX), and instant warm compresses combined with MGX, for treatment of dry eye disease (DED) due to meibomian gland dysfunction (MGD). In a prospective, multicenter, interventional study, 120 subjects with DED due to MGD were randomized 1:1 to an IPL arm or a control arm. Each subject was treated 3 times at 3-week intervals. The primary outcome measure was the tear break up time (TBUT). Tear break up time and a few additional outcome measures were evaluated at the baseline and at 3 weeks after the last treatment. All outcome measures improved in both arms, but in general, the improvement was significantly larger in the IPL arm. Tear break up time increased by 2.3±1.9 and 0.5±1.4 sec, in the IPL and control arms respectively (P<0.001). SPEED was reduced by 38% and 22% in the IPL and control arms, respectively (P<0.01). Meibomian Gland Yielding Secretion Score was improved by 197% in the IPL arm and 96% in the control arm. Corneal fluorescein staining also decreased by 51% and 24% in the IPL and control arms respectively, but the differences between the two arms were not statistically significant (P=0.61). A composite score of lid margin abnormalities improved in both arms, but more in the IPL arm (P<0.05). Intense pulsed light combined with MGX therapy was significantly more effective than instant warm compresses followed with MGX. This suggests that the IPL component has a genuine contribution to the improvement of signs and symptoms of DED.